Fine Particulate Matter (PM2.5) and Health Effects: An Unbridle Problem in Iran: - Baghbeheshti, Maryam; Zolfaghari, Mohammad; Rückerl, Regina (Galen Medical Journal, 2017)
Particulate matter (PM) is a complex mixture of solid and liquid particles from various sources. Fine PM or PM2.5 is defined as a mass with a size of less than 2.5 Î¼m in aerodynamic diameter and has a large contribution to the world increasing annually. Iran is a developing country set in the Middle East that is not secured from this pollutant mainly due to its industries, desert dust and the travel of dust from the neighboring countries. Poor air quality caused by PM2.5 can induce multiorgan dysfunction including cardiovascular disease, respiratory impairment, and other adverse effects that lead to morbidity and even death. Since PM2.5 is a risk factor for health problems, the comprehension of the detailed molecular mechanisms of PM2.5 including oxidative stress and inflammation would be beneficial. The aim of this review is gathering information from epidemiological studies about the health effects of this pollutant in Iran for the sake of a healthy environment and proposing solutions which can be applied to every country that is concerned about the air quality. [GMJ.2017;6(2):81-94]